5b=7+6b

Simple and best practice solution for 5b=7+6b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b=7+6b equation:



5b=7+6b
We move all terms to the left:
5b-(7+6b)=0
We add all the numbers together, and all the variables
5b-(6b+7)=0
We get rid of parentheses
5b-6b-7=0
We add all the numbers together, and all the variables
-1b-7=0
We move all terms containing b to the left, all other terms to the right
-b=7
b=7/-1
b=-7

See similar equations:

| -6h+10-6h=-8-10h | | 7-6v=-41 | | -4t=-5t+4 | | 3x=-6-3(2x+4)=x= | | 87=13+p | | -4(x-13)=8 | | h+6=2h | | 1-3j=-j-j-7 | | 2x+3(x-7)=4=x= | | 1=z-8/2 | | -2=6t-4 | | -10-(-2)=2x-4(x+2)+2x | | T=79=r | | 4f+2=552 | | 4t+10=t-8 | | 4t10=t-8 | | 3x-17=9x-7 | | x^2+3x-2=-1 | | (2+3x)+(x-22)=180 | | -11d=15.84-4.4d | | 2x+3=-6-3(2x+4)=x= | | 4-10x=-166 | | n÷3=13;n=39 | | 6+k=24 | | 4a-24=a | | y=180,000(1+.03)^10 | | -2-j=-20-9j+9j | | 7x=3(x-24)=x= | | 2(3-p)-17=40 | | 2(X-5)=4x+4-(5-X) | | -13z+12=-14z | | x‐7/4=‐2 |

Equations solver categories